0728 Physical and Mental Health among Blacks with OSA and Insomnia: a Stakeholder-engaged community study. (25th May 2022) - Rogers, April; Seixas, Azizi; Jin, Peng; Casimir, Georges; Nunes, Joao; Jean-Louis, Girardin
Abstract: Introduction: Health consequences of co-occurring obstructive sleep apnea (OSA) and insomnia have been well documented. However, little is known about the mental and physical consequences of co-occurring OSA and insomnia among Blacks. We aimed to investigate the rate of OSA risk and insomnia symptoms and potential associations with physical and mental health in a community sample of Blacks. Methods: Data were collected from an NIH-funded study 'Peer-Enhanced Education to Reduce Sleep Ethnic Disparities, designed to navigate blacks at risk of OSA to receive timely diagnosis and treatment using peer-delivered linguistically and culturally tailored sleep health education. Blacks (n=878) were screened for OSA using the Apnea Risk Evaluation System Questionnaire; a score ≥6 denoted high OSA risk. The Sleep Disorders Questionnaire was used to assess insomnia based on three common insomnia symptoms: trouble falling asleep, difficulty staying asleep, and early morning awakening. Physical Health Composite Score (SF-12PCS) and Mental Health Composite Scores (SF-12MCS) were generated based on how the person answered the SF-12 questions. Scores range from 0 to 100, where 0 indicates the lowest level of health and 100, the highest. Logistic regression models were used to assess associations of physical and mental health among Blacks at risk for OSA, reporting insomnia symptoms, and co-occurring OSA risk and insomnia symptoms. All models adjusted for differences in age, sex, and BMI.#8232; Results: The prevalence of OSA risk, insomnia symptoms, and co-occurring OSA risk and insomnia symptoms was 47.9%, 73.3%, and 40.2%, respectively. Logistic regression analyses showed lower physical score was positively associated with the odds of reporting insomnia symptoms (OR=1.03, p=0.007) and co-occurring OSA risk and insomnia symptoms (OR=1.02, p=0.001). Lower mental score was positively associated with the odds of OSA risk (OR=1.04, p=0.001), insomnia symptoms (OR=1.04, p=0.001), and co-occurring OSA risk and insomnia symptoms (OR=1.04, p=0.001). Individuals with OSA were less likely to report higher physical scores compared with those with co-occurring OSA risk and insomnia symptoms. Conclusion: Results demonstrate that blacks with insomnia symptoms are more likely to endorse worse physical and mental health. Future research should investigate further the mechanism underlying co-occurring OSA and insomnia in this population using objective measurements. Support (If Any): Support: NIH R01MD007716